Efficacy of Piperine for management of pulpal dental pain - Z Madani (Babol University of Medical Sciences, 2002)
Background and Objective: Management of painful irreversible pulpitis is one of the most common cases of dental emergencies. Since, in traditional medications, piperine was used for management of dental pain, this study was done to determine the efficacy of piperine plus pulpotomy for management of acute pulpal pain. Methods: In this study, 60 cases with a diagnosis of painful irreversible pulpitis were selected and divided into two groups. In case group, pulpotomy plus a pellet moistened with piperine was sealed in the chamber and in control group pulpotomy plus dry cotton pellet was sealed in the chamber. The efficacy of piperine was studied by Visual Analogue Pain Scale (Numerical 0-10) at 0, 2, 4, 8, 12, 24, 48 and 72 hours after the procedure. Findings: The results showed that there was not a significant difference in intensity of pain between control and case group at 2, 4 and 8 hours after treatment, but the intensity of pain was significantly lower in case group which piperine was used as a medicament. Conclusion: According to the results, it seems that piperine can be an effective medicament for management of acute pulpal pain.